Penggunaan Kata Emosi yang Menggambarkan Pengalaman Afeksi dalam Bakusedu - Darsita Suparno (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2017)
Bakusedu is vernacular language literature, such as short story is one of reality construction of Manado’s culture, in the form of oral and writing represented in symbols. For Manado’s people bakusedu is a kind of their societies’ advice which cannot be forgot and separated from their live; it also serves a means of social communication in order to teach, educate, to draw characters, emotion, and inform values for younger generation. This research’s problem is focused on the study of forms of emotion’s word and meaning in bakusedu which is spoken in Manado language. This research can be classified as a case study using eclectic approach which combines theories of linguistic and sociology of literature. Methodologically, in this research is natural in characteristics because the primary data are observed directly. The form of culture value in this bakusedu identified in writing. The researcher serves as human instrument. The data emotion words and phrases are gathered from monolog and dialog content of its bakusedu that is spoken by Manado ethnic group in North Sulawesi. The finding of emotion words and it function in the society are found, namely words and phrases which cover human character such as: working as mercy of god, discussion to solve problem, physical character; several kind of emotion words, such as positif, netral and negatif.